Competence, equipment and behavioural adaptation on Norwegian winter roads: A comparison of foreign and Norwegian HGV drivers. (February 2021) - Nævestad, Tor-Olav; Sagberg, Fridulv; Levlin, Gunhild; Bjørnskau, Torkel
Highlights: Foreign HGV drivers feel less safe and confident while driving under Norwegian winter conditions. This is related to vehicles, equipment, experience, training and competence. Foreign drivers are more likely to get stuck while driving uphill on winter roads. Supposedly as they drive more careful and slower than Norwegian HGV drivers. Norwegian HGV drivers feel safer and more confident while driving on winter roads. Abstract: There seems to be a widespread view that foreign lorry drivers' lack of competence on Norwegian roads, especially related to winter driving, is a significant safety problem. It has, however, been suggested that foreign heavy goods vehicle (HGV) drivers perform better than expected on Norwegian winter roads, as they feel less safe than Norwegian drivers, and adapt by driving slower and more carefully. The aim of the present paper is twofold. First, we examine whether foreign HGV drivers in Norway actually have poorer competence on, training for, experience with and equipment for winter driving than Norwegian HGV drivers. Second, we discuss whether the expected negative effect of these safety challenges is mitigated, as foreign HGV drivers adapt their behaviours. We use four data sources to shed light on the aims: (1) interviews, (2) roadside inspections, (3) small-scale survey and (4) towing incidents. Our data support the hypothesis about behavioural adaptation, indicating that foreign HGV drivers experience winter driving as more difficult or unsafe, as they have supposedly less suitable vehicles and equipment, less experience, training and competence for winter driving. They are therefore more likely to get stuck while driving uphill on winter roads, supposedly as they drive more carefully and slower than Norwegian HGV drivers. Norwegian HGV drivers feel safer and more confident while driving on winter roads, because of their equipment and their experience.